Advances in Applied Microbiology:Vol-53. - Laskin, Allen I;Ed. Bennett, Joan W;Ed (Advances in Applied Microbiology, v. 53, 2003)
Advances in Applied Microbiology offers intensive reviews of the latest techniques and discoveries in this rapidly moving field. The editors are recognized experts and the format is comprehensive and instructive.